Series of Chloranilate-Bridged Dinuclear Lanthanide Complexes: Kramers Systems Showing Field-Induced Slow Magnetic Relaxation - Ryuta Ishikawa; Shoichi Michiwaki; Takeshi Noda; Keiichi Katoh; Masahiro Yamashita; Satoshi Kawata (Magnetochemistry, 2019)
A series of chloralilate-bridged dinuclear lanthanide complexes of formula [{LnIII(Tp)2}2(μ-Cl2An)]·2CH2Cl2, where Cl2An2− and Tp− represent the chloranilate and hydrotris (pyrazolyl)borate ligands, respectively, and Ln = Gd (1), Tb (2), Ho (3), Er (4), and Yb (5) was synthesized. All five complexes were characterized by an elemental analysis, infrared spectroscopy, single crystal X-ray diffraction, and SQUID measurements. The complexes 1−5 in the series were all isostructural. A comparison of the temperature dependence of the dc magnetic susceptibility data of these complexes revealed clear differences depending on the lanthanide center. Ac magnetic susceptibility measurements revealed that none of the five complexes exhibited a slow magnetic relaxation under a zero applied dc field. On the other hand, the Kramers systems (complexes 4 and 5) clearly displayed a slow magnetic relaxation under applied dc fields, suggesting field-induced single-molecule magnets that occur through Orbach and Raman relaxation processes.